Generation and Manipulation of Superoscillatory Hotspots Using Virtual Fourier Filtering and CTF Shaping - Sanjeev, Abhijit; Shabairou, Nadav; Attar, Arrad; Scheberbaum, Daniel; Kapellner, Yuval; Sinvani, Moshe; Zalevsky, Zeev (Scientific Reports, 2020)
Superoscillation is a technique that is used to produce a spot of light (known as ‘hotspot’) which is smaller than the conventional diffraction limit of a lens and even smaller than the optical wavelength. Over the past few years, several techniques have been realized for the generation of the superoscillatory hotspot. In this article, for the first time to the best of our knowledge, we propose a novel and a more efficient technique for producing superoscillation in microscopic imaging by shaping the Coherent Transfer Function (CTF) of a lens via virtual Fourier filtering followed by a phase retrieval algorithm. We design and realize a phase mask which when placed at the pupil plane of a diffraction-limited lens produces a superoscillatory hotspot with sidelobes properly matched to the field of view (FOV) required in microscopic imaging applications, i.e. hotspot always coexists with huge intense rings known as ‘sidebands’ close to it and hence limiting the FOV. Our technique is also capable of extending the FOV with minimal loss in resolution of the hotspot generated and considerable ratio between the intensity of the hotspot to that of the side lobes while optimizing the obtainable FOV to the requirement of microscopy.
CRIS-Team Scopus Importer:2021-04-19